Valentino's syndrome: the red herring of a perforated viscus / Shaiful Amir Abdul Manap ... [et al.] - Abdul Manap, Shaiful Amir; Ahmad, Rabi'atul Adawiyah; Hashim, Hazzeq Safin; Mohd Razali, Mazuin (Faculty of Medicine, 2024)
Valentino's syndrome is a rare occurrence in which a perforated peptic or duodenal ulcer is mistaken as appendicitis. It occurs when the gastric and duodenal content tract along the right paracolic gutter and accumulate at the right lower abdomen causing irritation and inflammation to the surrounding area. The presentation can mimic acute appendicitis with tenderness at the right lower abdomen region. We present the case of a 35-year-old man who was diagnosed with perforated appendicitis but discovered a perforated peptic ulcer intraoperatively. Modified Graham's patch repair was successfully performed, and the patient's post-operative recuperation went smoothly. Valentino's syndrome is a deceptive condition that can lead to death if it is not correctly diagnosed and treated promptly. We emphasize the need to consider Valentino's syndrome as a differential diagnosis in patients with symptoms suggestive of appendicitis.